The Use of Academic Library Resources and Services by Undergraduate in Ibadan North Local Government of Nigeria - Awotola, Uche Caroline; Adewale, Olowolagba Jamie (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2018)
Libraries provide resources for knowledge acquisition, recreation, personal interests and interpersonal relationships for all categories of users. It enables the individual to obtain spiritual, inspirational, and recreational activities through reading, and therefore the opportunity of interacting with the society’s wealth and accumulated knowledge. This study examined the undergraduate students’ use of University library services and resources. It was affirmed the undergraduate utilized the University Libraries as learning centre. This was shown by the massive turn out to patronize the library services and resources weekly